Glamour in a Golden Age : Movie Stars of the 1930s - Ohmer, Susan; Lugowski, David; Larson, Allen; Knee, Adam; Hark, Ina Rae; Fuller-Seeley, Kathryn; Fischer, Lucy; Doty, Alexander; Desjardins, Mary; Creekmur, Corey K.; Castonguay, James; Becker, Christine; et al. (Book collections on Project MUSE., 2011)
Glamour in a Golden Age, incorporating archival and popular material, including fan and mass market magazines, other promotional and publicity material, and films themselves, presents original essays from eminent film scholars that analyze movie stars of the 1930s. Against the background of contemporary American cultural history, stardom is approached as an effect of, and influence on, the particular historical and industrial contexts that enabled these actors and actresses to be discovered, featured in films, publicized, and become recognized and admired--sometimes even notorious--par.